1998
DOI: 10.1002/(sici)1097-0215(19980130)75:3<467::aid-ijc22>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of primary cultures from human colonic tissue during tumor progression: Vitamin-D responses and vitamin-D-receptor expression

Abstract: Primary cultures derived from pre‐cancerous and cancerous human colon tissue are essential for understanding normal and abnormal growth function in the large intestine. Here presented are (i) the methodology for routine establishment of primary cultures of normal, adenoma‐ and carcinoma‐derived cells, and (ii) data for the apparently protective role of vitamin‐D compounds in colon carcinogenesis. The steroid hormone 1,25‐dihydroxyvitamin D3 and some non‐hypercalcemic analogs reduce the high mitotic rate of ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The active metabolite of vitamin D, 1a,25(OH) 2 D 3 , is readily able to initiate gene transactivation and acutely regulate proliferation of normal prostate, breast, and colon epithelial cells and myeloid CD 34-positive precursors (Konety et al, 1996;Ratnam et al, 1996;Tong et al, 1998;Rashid et al, 2001b;Zinser et al, 2002). By contrast, cancer and leukaemic cell lines from these tissues display a spectrum of sensitivities including complete insensitivity to 1a,25(OH) 2 D 3 , irrespective of VDR expression (Munker et al, 1986;Campbell et al, 1997;Kubota et al, 1998;Palmer et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The active metabolite of vitamin D, 1a,25(OH) 2 D 3 , is readily able to initiate gene transactivation and acutely regulate proliferation of normal prostate, breast, and colon epithelial cells and myeloid CD 34-positive precursors (Konety et al, 1996;Ratnam et al, 1996;Tong et al, 1998;Rashid et al, 2001b;Zinser et al, 2002). By contrast, cancer and leukaemic cell lines from these tissues display a spectrum of sensitivities including complete insensitivity to 1a,25(OH) 2 D 3 , irrespective of VDR expression (Munker et al, 1986;Campbell et al, 1997;Kubota et al, 1998;Palmer et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…There seems to be an inverse correlation between colorectal cancer incidence and sunlight exposure, low skin pigmentation, nutritional Vitamin D intake or serum levels of 25(OH)Vitamin D 3 [4,5]. Two decades of research yielded ample evidence for the anti-proliferative and proation of various established colon cancer cell lines [8][9][10] and primary cultures derived from human colon adenomas and carcinomas [11]. Exposure to calcitriol also induced the expression of differentiation markers such as brush border hydrolase, alkaline phosphatase and E-cadherin in colon cancer cells [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, Ro 23-7553 is as potent as 1α,25(OH) 2 D 3 in inhibiting proliferation but inferior in inducing apoptosis [24,25], whereas Ro 24-5531 is more potent [25]. Importantly, one study found these two compounds to be equivalent in growth inhibition, but Ro 24-5531 was more potent in inducing AP activity [26]. Ro 25-6760 induced growth inhibition 85% at 10 -6 M and induced apoptosis via increasing p21 protein levels [27].…”
Section: Unsaturated Side Chain Analoguesmentioning
confidence: 99%